Tailoring the crystallization behavior of poly(L-lactide) with self-assembly-type oxalamide compounds as nucleators: 1. Effect of terminal configuration of the nucleators. (September 2015) - Ma, Piming; Xu, Yunsheng; Shen, Tianfeng; Dong, Weifu; Chen, Mingqing; Lemstra, Piet J.
Graphical abstract: Highlights: Oxalamide compounds (NAs) are tailor-made as novel effective nucleators for PLLA. The end structure affects thermal behavior and nucleation efficiency of the NAs. The oxalamide compounds triggered "shish-kebab" morphology of PLLA crystals. The crystallization kinetics of PLLA was enhanced by the oxalamide compounds. Abstract: The bio-based and biocompostable semi-crystalline poly(L-lactide), PLLA, suffers from slow crystallization rate. Oxalamide compounds are tailor-made as novel self-assembly-type nucleators in this work, which altered significantly the crystallization kinetics of the PLLA. The terminal structures (cyclohexyl, benzyl and phenyl) show strong influence on their self-organization and nucleation efficiency. Their self-organizing temperature sequence (measured via rheology) in the PLLA melt is cyclohexyl > benzyl > phenyl ≈ 190 °C, while the nucleation activity follows a reverse order. Consequently, the compounds capped with phenyl group exhibit the highest nucleation efficiency. The oxalamide compounds in the PLLA melt showed varied depression in crystallization and dissolution temperatures, demonstrating a designable miscibility. Interestingly, the dissolved oxalamide compounds could organize into "shish-like" superstructures that subsequently triggered "shish-kebab" morphology of PLLA crystals free of any flow or shear. With the aid of phenyl-capped oxalamide compound (e.g. 0.75 wt.%), the crystallization of PLLA occurred at 108 °C with a crystallinity of 35% even upon fast cooling (20 °C/min), while the half-life crystallization time ( t 0.5 ) was dramatically reduced by 95% in a wide temperate range. In addition, the oxalamide compounds could significantly reduce the PLLA crystal size without modification on crystal form.